Text Mining Techniques for Information Extraction: Issues and Applications - Verma, Babita; Pillai, Jyothi (International Journal of Computer Sciences and Engineering, 2019)
ext mining research area has become very popular among researchers from various disciplines today. Text mining is one of the major areas of research for natural language documents. In this review, a comprehensive introduction and overview of text mining and existing research status is discussed. The major issue in text mining is the discovery of relevant information and patterns that are used to analyze text documents from the huge volume of information available over the internet. A number of tools and numerous methods exist for determining the relevant text and identifying valuable information for future research analysis and decision making. The correct and effective methods and tools for text mining helps in speed up the extraction of valuable information and it also decreases the effort and time required for the analysis. The paper describes the methods, applications and issues of text mining in various fields of life. These results based on the text mining information from the various cited research articles and publications will be very useful for the researchers working in this research area. In addition, various issues related to text mining are identified that affect the accuracy and relevancy of results.